Tinjauan Literatur: Efektivitas Penggunaan Metode Multisensori dalam Pembelajaran Membaca untuk Anak Disleksia di Sekolah Inklusi - Raudatul Jannah; Radiyatus Shalihah (PT. Penerbit Tiga Mutiara, 2025)
Dyslexia is a neurodevelopmental disorder that specifically affects an individual's ability to process phonological and orthographic information, thereby hindering the development of basic literacy skills. In inclusive education systems at the elementary level, these limitations are often not addressed through pedagogical approaches that align with the neurocognitive needs of learners. The problem addressed in this study is the effectiveness of the multisensory learning approach in improving the reading skills of children with dyslexia in inclusive elementary education settings. This research was conducted through a systematic literature review using a descriptive qualitative approach, drawing upon scholarly sources published in nationally and internationally accredited journals over the past decade. Thematic analysis was employed to identify consistent empirical findings related to multisensory interventions. The results show that the multisensory approach (which simultaneously engages visual, auditory, kinesthetic, and tactile modalities) has been proven to enhance phonological decoding, word recognition accuracy, reading fluency, and learning affectivity in children with dyslexia. Its effectiveness is highly influenced by the duration and intensity of the intervention, educators' competence in designing multisensory activities, and the suitability of materials to individual sensory profiles. The conclusion of this review asserts that the multisensory approach is not merely a remedial strategy, but a neuroeducation-based pedagogical framework that is inclusive and transformative. The novelty of this research lies in its integrative emphasis on the multisensory approach and principles of educational neuropsychology as the foundation for developing learning models that are responsive to the needs of neurodivergent learners in the context of inclusive elementary education in Indonesia.